Pulmonary Embolism in Patients with CKD and ESRD - Kumar, Gagan (American Society of Nephrology, 2012)
BACKGROUND AND OBJECTIVES: CKD and ESRD are growing burdens. It is unclear whether these conditions affect pulmonary embolism (PE) risk, given that they affect both procoagulant and anticoagulant factors. This study examined the frequency and associated outcomes of PE in CKD and ESRD. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: The Healthcare Cost and Utilization Project’s Nationwide Inpatient Sample was used to estimate the frequency and outcomes of PE in adults with CKD and ESRD. Hospitalizations for the principal diagnosis of PE and presence of CKD or ESRD were identified using International Classification of Diseases, Ninth Revision codes. Data from the annual US Census and US Renal Data System reports were used to calculate the number of adults with CKD, ESRD, and normal kidney function (NKF) as well as the annual incidence of PE in each group. Logistic regression modeling was used to compare in-hospital mortality among persons admitted for PE who had ESRD or CKD to those without these conditions. RESULTS: The annual frequency of PE was 527 per 100,000, 204 per 100,000, and 66 per 100,000 persons with ESRD, CKD, and NKF, respectively. In-hospital mortality was higher for persons with ESRD and CKD (P<0.001) compared with persons with NKF. Median length of stay was longer by 1 day in CKD and 2 days in ESRD than among those with NKF. CONCLUSIONS: Persons with CKD and ESRD are more likely to have PE than persons with NKF. Once they have PE, they are more likely to die in the hospital.